KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA SANGIR (ANALISIS KONTRASTIF) - LENGKOAN, VYONA EUNIKE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT The research is entitled ‘Interrogative sentences in English and Sangir Language. This study is an attempt to describe and analyze the English and Sangir Languagewhich focuses on the interrogative sentence in relation to their form and function in both languages based on Aarts and Aart’s theory and to compare by using Lado’s theory. The English and Sangir Languages are two languages from different language families. English is included in Indo-European and Sangir language is included in Austronesian one. Each of them has its own characteristic. The English data have been collected from books, whereas the data of Sangir language have been collected by interviewing some informants. The data are then analyzed and described using contrastive analysis approach. The result shows that forms of interrogative sentences in English are yes-no question, tag question and interrogative word question. English and Sangir language have similarities, in the form of yes-no question word is at the beginning of sentence and Sangir language at the beginning of sentence. The differences both languages are in form and function. In English has three form of interrogative sentences such as yes-no question, wh-question and tag question. Sangir language only has one question form such as Wh-question (Karapa, Koapa, Nikapura, Kangere, Suapa, Kosai). —————————————————————————————————————-Keywords : Interrogative sentences, English and Sangir Language, Contrastive Analysis.